Atypical Pathogenicity of Avian Influenza (H3N1) Virus Involved in Outbreak, Belgium, 2019 - Mieke Steensels (Emerging Infectious Diseases, 2020)
In 2019, an outbreak of avian influenza (H3N1) virus infection occurred among commercial poultry in Belgium. Full-genome phylogenetic analysis indicated a wild bird origin rather than recent circulation among poultry. Although classified as a nonnotifiable avian influenza virus, it was associated with reproductive tropism and substantial mortality in the field.